Ammunition leakage from military to civilian markets: market price evidence from Haiti, 2004–2012. Issue 7 (10th November 2019) - McDougal, Topher L.; Kolbe, Athena; Muggah, Robert; Marsh, Nicholas
ABSTRACT: The increase in the accessibility of firearms and ammunition represents a key factor of destabilization in many countries. It is also commonly associated with an escalation in intensity and organization of collective and interpersonal violence. In some cases, arms are illegally transferred via diversion from existing stores. In this article, we consider the leakage from military to civilian markets as an important source of ammunition available to civilians in Haiti. We employ a unique section-quarterly panel of ammunition prices on the Haitian civilian market over the period July 2004–July 2012. These data are combined with publicly available monthly data on authorized ammunition shipments to the country registered by the United Nations (UN) and Haitian National Police (HNP). We use a standard time-series Ordinary Least Squares (OLS) model to show that the exogenous shocks of UN- and HNP-ordered ammunition exert measurable downward pressure on civilian ammunition markets, which we calculate in terms of adjusted predictions and partial elasticities of demand. These effects constitute econometric evidence that the firewall that should in theory have separated military and civilian markets in Haiti partially broke down. We conclude with a suggestion for using this model to help estimate the specific size of the leakage.